Hubungan Terpaan Buzz Marketing Bocah Tembalang Terhadap Keputusan Follower Untuk Datang Ke Event Media Partner Bocah Tembalang Dengan Status Sosial Ekonomi Follower Sebagai Variabel Moderating - Elisabet .; Sunarto . (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Bocah Tembalang is a media buzzing that moves on the Instagram platform with a majority of followers who are students. Bocah Tembalang has done buzzing to attract consumers. But in reality there are several events that work together and entrust marketing to Bocah Tembalang and do not reach the desired visitor target. Therefore, this study wants to find out whether the exposure of Bocah Tembalang's marketing buzz has a relationship with the follower's decision to come to the media event for the partner of Bocah Tembalang. This study will also examine the relationship between the exposure of the Bocah Tembalang buzz marketing with the follower's decision to come to the Bocahg Tembalang media partner event with follower socio-economic status as a moderating variable. The theory used in this study is Elaboration Likelihood Theory. The type of research used is explanatory with a quantitative research method approach. The sampling technique in this study is by using non-probability sampling techniques with means of purposive sampling. Samples from this study were active followers of the Bocah Tembalang for the past year. The number of respondents is 100 peoples. Data analysis used in this research are the Kendall Tau-B correlation test and Kendall W. concordance. In this study it was shown that the exposure of the Bocah Tembalang marketing buzz about the media event of the Bocalang Tembalang partner was high due to the high followers of the Tembalang Boy who had access to information through the Tembalang Boy account. This can be seen from the number of visit followers in accessing the Tembalang Boy at a certain time The results of the first hypothesis test showed that the exposure of Buzz Marketing of the Bocah Tembalang (X) with the decision of the follower to come to the Bocah Tembalang media partner event (Y), obtained a correlation coefficient value of 0.70. with a strong level of correlation. The result of Z significance is 10.376, where Z count is greater than Z table 1%, which is 2.36 The results of the second hypothesis test showed the exposure of Buzz Marketing of the Bocah Tembalang (X) to the decision of the follower to come to the media event of the partner of Bocah Tembalang (Y) and the Follower Social Economic Status (Z), the correlation coefficient value was 0.39. These results indicate there is a positive relationship that is not significant with a very weak degree of closeness. In this study, it was also found that Bocah Tembalang a reliable level of information dissemination to followers so that Bocah Tembalang can be a good media partner in the company's media partner event.